Point Cumana, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Port of Spain, Trinidad., 2009)
A single house standing on the edge of the wooded coastline of Point Cumana and off in the distance, some of the islands that make up Trinidad's Five Islands.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Point Cumana; Coasts--Trinidad and Tobago; Trees--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Seashore--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); Dwellings--Trinidad and Tobago; Islands--Trinidad and Tobago; [1920]; Five Islands, The (Trinidad and Tobago)